Di- and tetra-nuclear oxorhenium(V) complexes of benzoylthiourea derivative ligands: Synthesis, structural characterization, and catalytic applications. (1st June 2022) - Keskin, Ebru; Solmaz, Ummuhan; Gumus, Ilkay; Arslan, Hakan
Graphical abstract: The new dinuclear and tetranuclear oxorhenium(V) complexes were synthesized. Dinuclear complexes transform into tetranuclear complexes in organic solvents. Single-crystal X-ray diffraction analysis was applied to identify the molecular structure. Mild, efficient, and rapid way of the sulfoxidation reaction with oxorhenium complexes was obtained. The pincer complex [Re V 2 O2 L 1 2 (OCH3 )2 ] showed the highest catalytic activity. Abstract: Two benzoylthiourea derivative compounds (H2 L 1 and H2 L 2 ) derived from isophthaloyl diisothiocyanate was prepared and applied as a ligand for the preparation of di- and tetra-nuclear oxorhenium(V) complexes. The reaction between ligands and tetrabutylammonium tetrachlorooxorhenate(V) in methanol was produced dinuclear oxorhenium(V) complexes {[Re V 2 O2 L 1 2 (OCH3 )2 ] (1 ) and [Re V 2 O2 L 2 2 (OCH3 )2 ] (2 )} with the expected metal:ligand ratio of 1:1. The tetranuclear complexes {[Re V 2 O2 L 1 2 -(µ-O)2 -Re V 2 O2 L 1 2 ] (1′ ) and [Re V 2 O2 L 2 2 -(µ-O)2 -Re V 2 O2 L 2 2 ] (2′ )} were obtained from the recrystallization of dinuclear complexes within a mixture of dichloromethane and acetonitrile solution. The prepared ligands and oxorhenium(V) complexes have been characterized by various techniques. The obtained metal complexes were also characterized by a single crystal X‐ray diffraction study. The obtained oxorhenium(V) complexes have been used as a catalyst for the oxidation of diphenyl sulfide. According to the results of the catalytic activity test obtained, these catalysts are very active for the oxidation of diphenyl sulfide. The best catalytic activity among the investigated complexes was also observed for [Re V 2 O2 L 1 2 (OCH3 )2 ] (1 ) by using 0.005 mmol catalyst loading at 1 h of reaction time, in chloroform solvent, and 2 equivalents of t BuOOH as an oxidant.